2017
DOI: 10.3389/fmars.2017.00021
|View full text |Cite
|
Sign up to set email alerts
|

Surface Gradients in Dissolved Organic Matter Absorption and Fluorescence Properties along the New Zealand Sector of the Southern Ocean

Abstract: The Southern Ocean plays a critical role in the global carbon cycle; dissolved organic matter (DOM), a component in the carbon cycling, can be characterized optically. Sea surface chromophoric dissolved organic matter (CDOM) absorption and fluorescence properties were examined in the New Zealand sector of the Southern Ocean (NZSSO) along a transect encompassing various hydrographic fronts associated with the Antarctic Circumpolar Current (ACC) during summer. Phytoplankton chlorophyll, dissolved organic carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
(144 reference statements)
0
9
0
Order By: Relevance
“…This is potentially due to low a CDOM for some samples, but many samples contained a CDOM (350) greater than 0.1 m −1 . This province is characterized by autochthonously produced CDOM, with a distinct S E 275:295 signal and a high correlation of a CDOM (325) with chlorophyll concentrations and upwelled waters transporting subsurface water with elevated levels of CDOM into the photic zone (D'Sa & Kim, ; Ortega‐Retuerta et al, , ). For many of these spectra, the lack of components is likely due to old, upwelled CDOM that behaves remarkably consistent across all spectral ranges, evidenced as an approximate one‐to‐one line in slope comparisons across different spectral ranges (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This is potentially due to low a CDOM for some samples, but many samples contained a CDOM (350) greater than 0.1 m −1 . This province is characterized by autochthonously produced CDOM, with a distinct S E 275:295 signal and a high correlation of a CDOM (325) with chlorophyll concentrations and upwelled waters transporting subsurface water with elevated levels of CDOM into the photic zone (D'Sa & Kim, ; Ortega‐Retuerta et al, , ). For many of these spectra, the lack of components is likely due to old, upwelled CDOM that behaves remarkably consistent across all spectral ranges, evidenced as an approximate one‐to‐one line in slope comparisons across different spectral ranges (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…CDOM absorption properties such as absorption coefficients at a specific wavelength and the slopes across specific regions of the optical absorption spectrum have been widely used to infer DOM sources and composition (Blough and Del Vecchio, 2002;D'Sa, 2008;Helms et al, 2008;D'Sa and DiMarco, 2009;Stedmon and Nelson, 2015;Hansen et al, 2016). CDOM abundance represented by absorption coefficient at 325 nm (a cdom 325) has been used to identify CDOM sources (Nelson et al, 2004), as a tracer of biochemical processes in the global ocean (Nelson et al, 2010;Catala et al, 2015) and to study its distribution and reactivity in the Southern Ocean (Ortega-Retuerta et al, 2010a;D'Sa and Kim, 2017). Absorption spectral indices such as the spectral slope S over narrow wavelength intervals (e.g., 275-295 nm; 350-400 nm) or their ratio (S R ) provide information on CDOM photo-oxidative state, molecular size distribution, and microbial activity (Helms et al, 2008(Helms et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The specific UV absorbance (SUVA) or the DOC normalized absorbance at 254 nm (SUVA 254 ) is a useful parameter for estimating the dissolved aromatic content in aquatic systems (Weishaar et al, 2003). Although CDOM optical properties have been widely used to characterize DOM in aquatic systems, only a few studies have been reported for the Southern Ocean, including regions in the Antarctic Peninsula and Australasian sector (Clementson et al, 2001;Ortega-Retuerta et al, 2009, 2010aDel Castillo and Miller, 2010) with limited measurements in the Ross Sea (Kieber et al, 2009;D'Sa and Kim, 2017). Experimental studies in the Southern Ocean waters around the Antarctic Peninsula have documented the photoreactive nature (photobleaching and photohumification) of CDOM (Ortega-Retuerta et al, 2010a), and contribution by bacterioplankton and Antarctic krill to CDOM and DOC (Ortega-Retuerta et al, 2009;Ruiz-Halpern et al, 2011), suggesting the important role of these processes in carbon cycling.…”
Section: Introductionmentioning
confidence: 99%
“…This is potentially due to low aCDOM for some samples, but many samples contained aCDOM(350) greater than 0.1 m -1 . This province is characterized by autochthonously produced CDOM, with a distinct S275:295 signal and a high correlation of aCDOM(325) with chlorophyll concentrations and upwelled waters transporting subsurface water with elevated levels of CDOM into the photic zone [D'Sa and Kim, 2017;Ortega-Retuerta et al, 2010;. For many of these spectra, the lack of components is likely due to old, upwelled CDOM that behaves remarkably consistent across all spectral ranges, evidenced as an approximate one-to-one line in slope comparisons across different spectral ranges (not shown).…”
Section: Gaussian Componentsmentioning
confidence: 99%
“…However, this relationship rapidly deteriorates as the terrestrial component of CDOM, shown to behave semi-conservatively with mixing , diminishes and gives way to in situ processes that both degrade and produce CDOM. Open ocean environments do not display a relationship between CDOM and DOC [D'Sa and Kim, 2017;, while the percent contribution of CDOM to the total DOM pool can be quite variable across environments but is generally relatively small in the global oceans [Nelson and Siegel, 2013].…”
Section: Introductionmentioning
confidence: 99%